After Welfare The Culture of Postindustrial Social Policy - Schram, Sanford F. (New York University Press, 2000)
Do contemporary welfare policies reflect the realities of the economy and the needs of those in need of public assistance, or are they based on outdated and idealized notions of work and family life? Are we are moving from a "war on poverty" to a "war against the poor?" In this critique of American social welfare policy, Sanford F. Schram explores the cultural anxieties over the putatively deteriorating "American work ethic," and the class, race, sexual and gender biases at the root of current policy and debates. Schram goes beyond analyzing the current state of affairs to offer a progressive alternative he calls "radical incrementalism," whereby activists would recreate a social safety net tailored to the specific life circumstances of those in need. His provocative recommendations include a series of programs aimed at transcending the prevailing pernicious distinction between "social insurance" and "public assistance" so as to better address the needs of single mothers with children. Such programs could include "divorce insurance" or even some form of "pregnancy insurance" for women with no means of economic support. By pushing for such programs, Schram argues, activists could make great strides towards achieving social justice, even in today's reactionary climate